Catalysis in the Service of Green Chemistry: Nobel Prize-Winning Palladium-Catalysed Cross-Couplings, Run in Water at Room Temperature: Heck, Suzuki-Miyaura and Negishi reactions carried out in the absence of organic solvents, enabled by micellar catalysis - Lipshutz, Bruce H. (2012)
Palladium-catalysed cross-couplings, in particular Heck, Suzuki-Miyaura and Negishi reactions developed over three decades ago, are routinely carried out in organic solvents. However, alternative media are currently of considerable interest given an increasing emphasis on making organic processes ‘greener’; for example, by minimising organic waste in the form of organic solvents. Water is the obvious leading candidate in this regard. Hence, this review focuses on the application of micellar catalysis, in which a ‘designer’ surfactant enables these award-winning coupling reactions to be run in water at room temperature.